Հայկական հարցի միջազգայնացման խնդիրը հասարակական մտքի և պատմագիտության մեջ - Գևորգ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Проблема интернализации Армянского вопроса тесно связана с насущными национальными вопросами армянского народа, в силу чего история ее изучения особенно актуальна для арменоведения. Причины интернализации Армянского вопроса, отношение великих держав к Османской Турции, внешнеполитическая ориентация армян неоднократно рассматривались в исторических исследованиях. Исходя из идеологического диктата, советская историография, за редкими исключениями, рассматривала интернализацию Армянского вопроса либо в качестве второстепенного звена Восточного вопроса, либо в отрыве от проводимой османскими властями политики. Широкое обсуждение рассматриваемой проблемы способствует ее правдивой и объективной оценке. The issue of the internalization of the Armenian question is tightly connected with the current national issues of Armenian people. So, this study is very vital for the complex of Armenian studies. The reasons of the internalization of the Armenian question, the position of great powerful countries regarding Ottoman Turkey, external political orientation of Armenians were thoroughly observed in various historic researches. The Soviet historiography (here we must take into consideration the ideological conditions), with only some exceptions, used to observe the internalization of the Armenian question either as an issue in the context of Eastern question, or a separate issue of the policy, realized by Ottoman politicians. The thorough discussion of the problem supports greatly to discover the true sides and purposes of this task.
Keywords: History; Political Science; D History; J Political Science